1991
DOI: 10.1161/01.cir.83.6.1880
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of edema in constrictive pericarditis. Studies of body water and sodium, renal function, hemodynamics, and plasma hormones before and after pericardiectomy.

Abstract: The restricted distensibility of the atria, in constrictive pericarditis, limits the secretion of atrial natriuretic factor and, thus, reduces its natriuretic and diuretic effects. This results in retention of water and sodium greater than that occurring in patients with edema from myocardial disease. The arterial pressure is maintained more by the expansion of the blood volume than by an increase in the peripheral vascular resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0
2

Year Published

1993
1993
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 15 publications
1
48
0
2
Order By: Relevance
“…Therefore, most of these data need to be set aside. In the late 1980s and early 1990s, a series of studies was done on patients with severe chronic low-or high-output HF who had never received any form of pharmacological treatment (26)(27)(28)(29)(30)(31). Because these patients were untreated, it can be assumed that the insights into the mechanisms being tested were not being confounded by the effects of drugs.…”
Section: Role Of Hemodynamic Abnormalities In the Pathogenesis Of Crsmentioning
confidence: 99%
“…Therefore, most of these data need to be set aside. In the late 1980s and early 1990s, a series of studies was done on patients with severe chronic low-or high-output HF who had never received any form of pharmacological treatment (26)(27)(28)(29)(30)(31). Because these patients were untreated, it can be assumed that the insights into the mechanisms being tested were not being confounded by the effects of drugs.…”
Section: Role Of Hemodynamic Abnormalities In the Pathogenesis Of Crsmentioning
confidence: 99%
“…Chronic obstructive pulmonary disease Braunstein et al [6] In the Medicare study 26% of the patients had COPD Gustafsson et al [9] In the Danish Diamond study 22% had COPD Ni et al [53] In this study only 10% had COPD McCullough et al [54] In this Emergency department study 21% of the patients had COPD Anemia Tanner et al [59] The prevalence of anemia was 15% Ezekowitz et al [60] The prevalence of anemia was 17% Silverberg et al [61] The prevalence of anemia was 50% and in patients with severe HF 80% Komajda [62] In this review the prevalence of anemia and its clinical characteristics are discussed Efficacy of heart failure treatment similar in diabetic and nondiabetic patients Rydén et al [28] Similar effect in the ATLAS study as in the SOLVD study (Shindler et al [25]) CIBIS II trial [49] Similar results in the CIBIS II-study evaluating the effect of a beta-blocker The Task force of the ESC [50] Loop-diuretics are recommended instead of thiazide diuretics in patients with diabetes, because of the hypothesis that thiazide diuretics may impair the metabolic state in diabetic patients Herings RBM et al [51] Since it has been reported hypoglycemia in connection with treatment with ACE-inhibitors careful monitoring is recommended Malmberg et al [52] Aggressive insulin treatment has not been performed in patients with heart failure but in patients with acute myocardial infarction and with a favourable outcome Chronic obstructive pulmonary disease Gosker et al [56] If use of beta-blockers beta-1 selective beta-blockers as bisoprolol is recommended Salpeter et al [57] Similar results shown in this meta-analysis, beta-1-selective beta-blockers are recommended Anemia Anand et al [72] Blood transfusions have shown beneficial effects in terms of clinical improvement Low-Friedrich et al [74] Administration of erythropoietin has beneficial effects in terms of unloading the heart Silverberg et al [66] Administration of erythropoietin together with intravenous iron improve cardiac and renal function, NYHA functional class and morbidity (reduce heavily the number of hospitalisations due to heart failure)…”
Section: Study Resultsmentioning
confidence: 63%
“…Studies using blood-transfusions to correct the developed anemia in patients with HF have shown beneficial effects in terms of clinical improvement [72]. Moreover, it is important to correct the anemia in order to improve the prognosis of the patients.…”
Section: Correction Of Anemiamentioning
confidence: 99%
“…Improvement in symptoms and normalization of cardiac pressures may occur within a few months after pericardiectomy (14). As for patients in functional class I with no clinical signs of heart failure, pericardiectomy is not to be recommended (9).…”
Section: Discussionmentioning
confidence: 99%